JEJAK MOCH. ICHSAN NUR ROMADHON DI PENCAK SILAT - IRHAN WIJAYA, YOGA; HERDYANTO, YONNY (Jurnal Prestasi Olahraga, 2018)
A very proud achievement that the guidance of pencak silat in the regions so much that the rise of new junior athletes. But in building an organization is not as easy as turning the palm of the hand, in an organization the role of a coach is very important to create athletes achievement. Athlete is someone who has a special ability in one sport. But to be an athlete is not easy, must have good skills and abilities in the sports that they do. Various relevant abilities have a great influence in supporting the athletes ability, then the athlete must be tolalitas in practice. This is very necessary, because athletes are an integral part with a competition, competition, hard work, and pride of each region as well as the pride of the country in an international event. Moch. Ichsan Nur Romadhon is a remarkable athlete figure, his work bebagai altlet pencak silat no doubt. His love and seriousness in the world of martial arts is evidenced by continuing to practice to achieve achievement to the international level. Various achievements, especially pencak silat pencak has been achieved. Achievement is he got because of his great enthusiasm and persistence in practice. Moch. Ichsan Nur Romadhon has won the best Indonesian football competition in the adult KEJURNAS IPSI. The purpose of this research is to know the profile, the achievement journey as well as the view of the people around it about the achievement that Moch achieves. Ichsan Nur Romadhon. This type of research is qualitative by using descriptive method. The location of data collection is done conditionally by adjusting the situation and condition of research subject. With the subject of research is Moch. Ichsan Nur Romadhon. The results of data processing is done by using data analysis through interviews with research subjects, achievement as an Indonesian martial art athlete achieved by Moch. Ichsan Nur Romadhon, parents, coaches and friends in the arms of Moch. Ichsan Nur Romadhon. The conclusion in this research has got the result that to become Indonesian pencak silat athlete who always reach the champion and get best football predicate in Indonesia is must have high willingness, hard work, diligent, always learn, discipline and, believe in the prayer of both parents .Keywords: Profile, Achievement, Athlete, Coach, Pencak SilatSuatu prestasi yang sangat membanggakan bahwa pembinaan pencak silat di daerah-daerah begitu banyak sehingga memunculkan atlet-atlet junior baru. Namun dalam membangun suatu organisasi tidaklah mudah seperti membalikan telapak tangan, dalam suatu organisasi peranan seorang pelatih sangatlah penting untuk menciptakan atlet berprestasi.Atlet merupakan seseorang yang memiliki kemampuan khusus dalam salah satu cabang olahraga. Namun untuk menjadi seorang atlet tidaklah mudah, harus memiliki skill dan kemampuan yang bagus didalam cabang olahraga yang digelutinya.Berbagai kemampuan yang relevan memiliki pengaruh besar dalam menunjang kemampuan atlet, maka atlet harus tolalitas dalam berlatih. Hal ini sangat diperlukan, karena atlet merupakan bagian yang tidak terpisahkan dengan suatu kompetisi, persaingan, kerja keras, serta kebanggaan suatu daerah masing-masing maupun kebanggaan negara dalam suatu even internasional. Moch. Ichsan Nur Romadhon adalah sosok atlet yang luar biasa, kiprahnya bebagai altlet pencak silat tidak diragukan lagi. Kecintaan dan keseriusannya pada dunia pencak silat dibuktikan dengan terus berlatih untuk mencapai prestasi hingga level internasional. Berbagai prestasi gemilang khususnya pencak silat telah diraihnya. Prestasi tersebut dia dapatkan karena semangatnya yang besar serta kegigihannya dalam berlatih. Moch. Ichsan Nur Romadhon pernah meraih predikat pesilat terbaik se-Indonesia di KEJURNAS IPSI dewasa.Kata kunci :Profil, Prestasi, Atlet, Pelatih, Pencak Silat.